Concentration-QT Modeling Following Inhalation of the Novel Inhaled Phosphodiesterase‐4 Inhibitor CHF6001 in Healthy Volunteers Shows an Absence of QT Prolongation - Koen Jolling; Angela Äbelö; Nicolas Luyckx; Marie‐Anna Nandeuil; Mirco Govoni; Massimo Cella; Andreas Lindauer (Wiley, 2019)
Concentration‐QTcF data obtained from two phase I studies in healthy volunteers treated with a novel phosphodiesterase‐4 inhibitor currently under development for the treatment of chronic obstructive pulmonary disease were analyzed by means of mixed‐effects modeling. A simple linear mixed‐effects model and a more complex model that included oscillatory functions were employed and compared. The slope of the concentration‐QTcF relationship was not significantly greater than 0 in both approaches, and the simulations showed that the upper limit of the 90% confidence interval around the mean ΔΔQTcF is not expected to exceed 10 ms within the range of clinically relevant concentrations. An additional simulation study confirmed the robustness of the simple linear mixed‐effects model for the analysis of concentration‐QT data and supported the modeling of data obtained from studies with different designs (parallel and crossover).